2016
DOI: 10.1007/s40279-016-0546-5
|View full text |Cite
|
Sign up to set email alerts
|

Is There Evidence that Runners can Benefit from Wearing Compression Clothing?

Abstract: Our present findings suggest that by wearing compression clothing, runners may improve variables related to endurance performance (i.e., time to exhaustion) slightly, due to improvements in running economy, biomechanical variables, perception, and muscle temperature. They should also benefit from reduced muscle pain, damage, and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
84
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 59 publications
6
84
1
Order By: Relevance
“…This finding is in agreement with previous research, with a recent review of 32 trials using CG during or after running reporting insignificant effects on recovery [37]. An earlier review of 23 peer-reviewed papers, 11 of which were studies on recovery from running, also found insignificant effects from CG [39].…”
Section: Compression Power Recovery and Runningsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is in agreement with previous research, with a recent review of 32 trials using CG during or after running reporting insignificant effects on recovery [37]. An earlier review of 23 peer-reviewed papers, 11 of which were studies on recovery from running, also found insignificant effects from CG [39].…”
Section: Compression Power Recovery and Runningsupporting
confidence: 91%
“…Despite the prevailing consensus shifting in favour of CG as a recovery aid [9,22,36], recent reviews highlight inconsistent and variable results [9,14,34,37]. For example, the recovery of strength has been frequently improved by CG at time-points over 24 h, with reported benefits over controls consistently ranging from between 5% and 10% [9,19,21,34,38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the literature specific to post-exercise recovery, various outcomes have been reported, with no or small beneficial effects in physiological, psychological, or biomechanical parameters (Engel et al, 2016). Wearing compression garments during running exercise was associated with improvements in muscle oxygenation during intermittent high intensity running (Sear et al, 2010), leg volume (Bovenschen et al, 2013), muscle damage using magnetic resonance imaging and histochemical techniques (Valle et al, 2013), delayed onset of muscle soreness (DOMS, see Duffield and Portus, 2007), and heart rate (Varela-Sanz et al, 2011).…”
Section: Introductionsupporting
confidence: 55%
“…Evidence of the efficiency of compression garments in recovery is solid with recent meta-analysis, which confirms that compression alleviates symptoms associated with fatigue (6)(7)(8). Suggested mechanisms include enhanced venous return and blood flow in passive conditions (9,10) that may help eliminate metabolic waste (11,12), improve muscle oxygenation (13,14) and limit edema / inflammation (15,16) as well as delayed onset muscle soreness (DOMS) (6,7).…”
Section: Introductionmentioning
confidence: 88%